Retrospective use of whole genome sequencing to better understand an outbreak of Salmonella enterica serovar Mbandaka in New South Wales, Australia - Cassia Lindsay; James Flint; Kim Lilly; Kirsty Hope; Qinning Wang; Peter Howard; Vitali Sintchenko; David N Durrheim (World Health Organization Regional Office for the Western Pacific, 2018)
Introduction: Salmonella enterica serovar Mbandaka is an infrequent cause of salmonellosis in New South Wales (NSW) with an average of 17 cases reported annually. This study examined the added value of whole genome sequencing (WGS) for investigating a non-point source outbreak of Salmonella ser. Mbandaka with limited geographical spread. Methods: In February 2016, an increase in Salmonella ser. Mbandaka was noted in New South Wales, and an investigation was initiated. A WGS study was conducted three months after the initial investigation, analysing the outbreak Salmonella ser. Mbandaka isolates along with 17 human and non-human reference strains from 2010 to 2015. Results: WGS analysis distinguished the original outbreak cases (n = 29) into two main clusters: Cluster A (n = 11) and Cluster B (n = 6); there were also 12 sporadic cases. Reanalysis of food consumption histories of cases by WGS cluster provided additional specificity when assessing associations. Discussion: WGS has been widely acknowledged as a promising high-resolution typing tool for enteric pathogens. This study was one of the first to apply WGS to a geographically limited cluster of salmonellosis in Australia. WGS clearly distinguished the outbreak cases into distinct clusters, demonstrating its potential value for use in real time to support non-point source foodborne disease outbreaks of limited geographical spread.